Application of Probit Analysis in Studying the Allelopathy Phenomenon - Dafaallah, Awadallah Belal (Iraqi Journal of Science, 2020)
Probit analysis is a type of regression used to analyze the relationship between a stimulus and the quantal response. Allelopathy refers to direct or indirect negative or positive effects of one plant on another through the release of chemical compounds into the environment. This study was carried out to apply probit analysis in investigating the allelopathic effects of the leaves aqueous extracts of apple of Sodom [Calotropis procera (Aiton) W.T.] on the inhibition of seed germination of African rattlebox (Crotalaria saltiana Andr.). A laboratory experiments were carried out at the Faculty of Agricultural Sciences, University of Gezira, Sudan in season 2014/15. Ten concentrations (2.3, 4.6, 7.0, 9.3, 11.6, 13.9, 16.2, 18.5, 20.8 and 23.2 g/l) leaves aqueous extract of apple of Sodom were prepared from the stock solution (50 g / l). A control with sterilized-distilled water was included for comparison. Treatments were arranged in completely randomized design with four replicates. The seeds were examined for inhibition (%) in germination at three days after initial germination. Collected data were transformed using Abbott’s formula and subjected to probit analysis procedure (P £ 0.5). The results showed that the leaves aqueous extract of apple of Sadom had allelopathic effects on seed germination of African rattlebox and there was direct positive relationship between concentration (g/l) and inhibition (%). Also, the data indicated that plotting of corrected inhibition (%) against concentration (%) formed a sigmoid curve. Probit analysis transformed the sigmoid concentration-response curve to a straight line. Hence, the LC25 (2.16 g/l), LC50 (8.55 g/l) and LC75 (33.88 g/l) were accurately estimated. It was concluded that probit analysis is appropriate procedure in studying the allelopathy phenomenon.